PO 104 - EAGLE SYNDROME: A CAUSE OF LIFE-THREATENING ANESTHETIC CHALLENGES - A CASE REPORT - Barbosa, Helena; Martins, Mafalda; Coroa, Mariana; Brás, Alice; Ribeiro, Edite (Journal of the Portuguese Society of Anesthesiology, 2023)
x